2019
DOI: 10.1101/2019.12.18.19014340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dose–response relationship between physical activity and mortality in adults with noncommunicable diseases: A systematic review and meta-analysis of cohort studies

Abstract: Objective To investigate the relationship between post-diagnosis physical activity and mortality in patients with selected noncommunicable diseases, including breast cancer, lung cancer, type 2 diabetes (T2D), ischemic heart disease (IHD), chronic obstructive pulmonary disease (COPD), stroke, osteoarthritis, low back pain and major depressive disorders. Design Systematic review and dose-response meta-analysis. Data sources PubMed, Scopus and the Web of Science were searched systematically for English publicati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…It is clear that the overall goal of exercise in diabetes management is to decrease physical inactivity, exercise and the afore mentioned interventions all decrease physical inactivity. Higher levels of physical activity are associated with lower mortality rates in T2D (Geidl et al, 2020). Finally, we have not addressed adherence and barriers to exercise or the aforementioned interventions.…”
Section: Limitationsmentioning
confidence: 99%
“…It is clear that the overall goal of exercise in diabetes management is to decrease physical inactivity, exercise and the afore mentioned interventions all decrease physical inactivity. Higher levels of physical activity are associated with lower mortality rates in T2D (Geidl et al, 2020). Finally, we have not addressed adherence and barriers to exercise or the aforementioned interventions.…”
Section: Limitationsmentioning
confidence: 99%
“…7 Individual and regular physical education reduce mortality in both healthy adults and adults with chronic pulmonary and other diseases. 8 As COPD is not reversible and lung function will not improve, HRQoL is a key, modifiable patient-centered factor for health outcomes. 9 Also, for many VTE patients, impaired HRQoL is an important marker for clinically relevant outcomes such as overall mortality.…”
Section: Vte Copd Physical Activity and Quality Of Lifementioning
confidence: 99%
“…Studies have demonstrated that a decrease in moderate to vigorous physical activity (MVPA) over a 30-year period is associated with increased odds of developing diabetes (9). Moreover, it has been found that mortality rates in patients with diabetes decrease by approximately 4% for every 10 METs per hour/week increase in physical activity (10). Thus, physical activity in diabetic individuals is a nonpharmacological treatment protecting from major diabetes-related complications (5).…”
Section: Introductionmentioning
confidence: 99%